AKUNTABILITAS PARTAI POLITIK DI KOTA SEMARANG: KAJIAN PELAKSANAAN AKUNTABILITAS PADA PARTAI DEMOKRAT DI KOTA SEMARANG TAHUN 2009-2014 - Dzunuwanus Ghulam Manar (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2016)
Accountability is an important instrument within democratic practice. It provides guarantee of the promises and acts of politicians, member of parliament, and elected public official. Partai Demokrat (Democratic Party) as a ruling party in 2009 election of Semarang Municipality does not contributes significant practice of accountability. The research provides evidence that accountability is well known and understood by member of parliament from Partai Demokrat. However, it failed taking into practice.